PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP RETENSI KARYAWAN PADA RAZ HOTEL AND CONVENTION JL. DR. MANSYUR NO. 168 MEDAN - Tanjung, Dinda Sari; Syahreza, Dina Sarah (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan, 2017)
This study aims to determine the effect of compensation and working environment on the retention of employees at RAZ Hotel & Convention Medan. The sample in this study amounted to 66 employees. The sampling technique using the entire amount of the population in this study, called the study population. Validity of test results obtained radding Ë rtable for each item statement and reliability test questionnaire obtained a Cronbach alpha of each variable are: 0.803 for the variable X1, 0,887 for the variable X2 Â , and 0,821 for the variable Y. This value is greater than the significance level rtable is 0,361. The data analysis technique used mainly in this research is multiple regression analysis with the formula Y = a + b1x1 + b2x2 + e. From the research conducted found Y = 9,020 + 0,324x1 + 0,387x2 + e. With a coefficient of determination (R2) of 0,417. Which means the X1 and X2 explain the effect on variable Y of 41,7% while the remaining 58,3% is explained variables outside the company. Rated tadding partial test variable compensation 2,332 Ë 1,998 that significant values of 0.023 Ë 0.05. Tadding work environment thatÂ 4.716 Ë 1.998 significant value of 0.000 Ë 0.05. Which means simultaneously variable compensation and work environment partially positive and significant effect on the retention of employees in RAZ Hotel & Convention Medan. The resulting simultaneous test of the calculation is equal to 22,562 with a Ftable = 3,150, which means Fadding Ë Ftable with level of significant (Î±) 0,000 Ë 0.05, which means that the hypothesis is accepted that compensation and working environment together significant effect on employee retention in RAZ Hotel & Convention Medan.Â Keywords: Compensation, Work Environment, Employee Retention